Dynamics and dependencies of the configuration-dependent 1–2 kHz fluctuation in W7-X. (June 2021) - Ballinger, S.B.; Terry, J.L.; Baek, S.G.; Beurskens, M.; Brunner, K.J.; Fuchert, G.; Knauer, J.; Killer, C.; Pasch, E.; Rahbarnia, K.; Schilling, J.; Scott, E.; et al.
Highlights: A 1–2 kHz fluctuation observed in W7-X is studied using cameras, probes, and magnetic coils. The fluctuation appears to rotate poloidally in the E × B direction between 1 and 10 km/s. The strength of the fluctuation depends on several plasma and machine parameters. Abstract: A 1–2 kHz electromagnetic mode is present in a large fraction of W7-X discharges in the standard magnetic field configurations with 5/5 edge island structure. The power in the mode is significantly reduced in other magnetic configurations. The mode can appear spontaneously and persist for the full duration of a discharge. Its full width at half maximum is typically 100–300 Hz. The 1–2 kHz mode was first observed in visible light emissions from the divertor [1] . Matching spectral peaks were found in measurements of both global and edge plasma parameters, including line-integrated density, diamagnetic energy, and edge floating potential and ion saturation current [2] . An infrared camera recording shows a temperature modulation of 2.5 K due to this mode on a divertor tile where the average temperature was 600 °C. Separate correlation analyses of the high-speed camera recordings, Langmuir probe signals, and Mirnov coil signals all indicate a poloidal velocity of 0.5–10 km/s and m = 2 as a likely poloidal mode number. Langmuir probes mounted on the Multi-Purpose Manipulator show that the fluctuation is present in one of the magnetic islands over a radial distance of at least 5 mm. A database of various diagnostic measurements and dB/dt signals from a Mirnov coil was created using a majority of the discharges from the 2018 campaign on W7-X, in order to shed light on the plasma parameters that are correlated with the existence of the 1–2 kHz mode. The power in the mode is positively correlated to the toroidal current, total external heating power, and core electron temperature. It is negatively correlated with plasma density.